Financial Incentives to Increase Utilization of Reproductive, Maternal, and Child Health Services in Low- and Middle-Income Countries : A Systematic Review and Meta-Analysis - Neelsen, Sven; de Walque, Damien; Friedman, Jed; Wagstaff, Adam (World Bank, Washington, DC, 2021)
Financial incentives for health providers and households are increasingly used to improve reproductive, maternal, and child health service coverage in low- and middle-income countries. This study provides a quantitative synthesis of their effectiveness. A systematic review was conducted of the effects of performance-based financing, voucher, and conditional cash transfer programs on six reproductive, maternal, and child health service indicators, with eligible evidence coming from randomized controlled trials and studies using double-difference, instrumental variables, and regression discontinuity designs. Four literature searches were conducted between September 2016 and March 2021 using seven academic databases, Google Scholar, development agency and think tank websites, and previous systematic reviews. Random effects meta-analysis was used to obtain mean effect sizes. From 58 eligible references 212 impact estimates were extracted, which were synthesized into 130 program-specific effect sizes. Financial incentives increase coverage of all considered reproductive, maternal, and child health indicators, but mean effects sizes are of modest magnitude. Effect size heterogeneity is typically low to moderate, and there is no indication that study bias risk, baseline indicator levels, or a combination of provider- and household-level incentives impact effect sizes. There is, however, weak evidence that mean effect sizes are somewhat smaller for performance-based financing than for voucher and conditional cash transfer programs, and that the increase in income, rather than the incentive itself, drives coverage improvements. Financial incentives improve reproductive, maternal, and child health service coverage. If future research confirms the preliminary finding that performance-based financing has smaller effects, voucher and conditional cash transfer programs are the preferred policy option among incentive interventions to achieve higher reproductive, maternal, and child health service coverage. The relative effectiveness and efficiency of incentives compared with unconditional increases of provider and household incomes, however, need to be studied further.